A new species and new records of microcaddisflies (Trichoptera: Hydroptilidae) from northeastern Brazil - de Souza, Wagner Rafael M.; Santos, Allan Paulo Moreira; Lima, Lucas R.c.; Pinheiro, Ulisses (Zootaxa, 2013)
The Hydroptilidae constitute the most diverse and widespread family of Trichoptera in the world. About 90 species of microcaddisflies have been recorded from Brazil, but the northeastern region is one of the least-sampled. In this work we describe a new species of Metrichia from Pernambuco State. Furthermore, we present the first records of Flintiella andreae Angrisano 1995 and Oxyethira bettyae Thomson & Holzenthal 2012 from Brazil, and four other new records from the northeastern region.